Hypoxia‐induced endothelial cell responses – possible roles during periodontal disease. Issue 6 (14th December 2018) - Mendes, Reila T.; Nguyen, Daniel; Stephens, Danielle; Pamuk, Ferda; Fernandes, Daniel; Hasturk, Hatice; Van Dyke, Thomas E.; Kantarci, Alpdogan
Abstract: Background and objective Inflammatory periodontal pockets are known to be hypoxic. Hypoxia influences vascular response to periodontal inflammation, including angiogenesis, which is critical for oxygen and nutrient delivery to periodontal tissues and granulation tissue formation. Our previous work suggests that periodontal bacteria may actively contribute to pocket hypoxia. Herein, we test the hypothesis that Fusobacterium nucleatum actively induces low oxygen tension, which modulates angiogenesis and endothelial cell activity. HUVEC cells were incubated in 1.5% oxygen for (Folkman & Shing, 1992)48 hours. Cell proliferation was measured by MTT; surface expression of CD31, CD34 and VEGF receptors (VEGFR1, VEGFR2) were analyzed by FACS. mRNA expression of HIF isoforms, iNOS, eNOS, COX‐2, and VEGF was measured by quantitative PCR. Supernatants were analyzed for the release of IL‐1α, TNF‐α, and VEGF by ELISA or multiplex immunoassays and nitric oxide was measured by colorimetric assay. F. nucleatum actively depleted oxygen. Hypoxia resulted in a significant increase of HIF isoforms. iNOS was increased while nitric oxide was unchanged. VEGF release was increased at 4 hours followed by an increase in VEGFR1 at 12 hours, but not VEGFR2. CD31 expression was reduced and CD34 was increased after 48 hours ( p  < 0.05). IL‐1α and TNF‐α release were decreased at 4 hours (p < 0.05), but both increased by 24 hours; TNF‐α increased at 24 h. The data highlight the role of hypoxia in endothelial cell inflammatory changes. F. nucleatum, considered a bridging species in the development of periodontopathic biofilms induces hypoxia in the periodontium leading to angiogenic changes in periodontal disease pathogenesis.